Current practices of Western Australian general dentists regarding management of patients on anticoagulant/antiplatelet therapy. (5th July 2021) - Foo, M; See, L; Lee, J; Feng, B; Kruger, E
Abstract: Purpose: Currently, there are little to no published studies outlining general dentists' knowledge in the management of patients on anticoagulant/antiplatelet therapies in Australia. The aim of this study was to investigate the current practices of Western Australian (WA) general dentists with regards to dental management of patients taking anticoagulants/antiplatelets. Materials and methods: WA dentists were invited to undertake a survey to investigate their knowledge on the management of patients taking anticoagulant/antiplatelet. The questionnaire provided to WA general dentists consisted of pre‐extraction advice on patients (direct oral anticoagulants [DOACs], antiplatelets, warfarin, dual antiplatelets and antiplatelet/anticoagulant). Results were analysed using descriptive statistics as well as chi‐square tests. Results: Of the 89 participants, 40.5% had <5 years of general dental experience. Most WA general dentists (64%–71%) responded with 'no change' when performing extractions on patients on DOACs, antiplatelet therapy, warfarin, dual antiplatelets and antiplatelets/anticoagulants ( P = 0.00). Furthermore, dentists with 6–10 years of experience were more likely to cease antiplatelet for 24 h before extractions ( P < 0.05). Dentists who extracted 10–30 teeth per month were likely to stop antiplatelets and DOACs for more than 48 h compared to other groups ( P < 0.05). Conclusion: Most WA dentists would not cease anticoagulant/antiplatelet therapy when undergoing dental extractions.